Constitution writing, religion and democracy - Bali, Asli Ummuhan; Lerner, Hanna (Cambridge University Press, 2017)
This book explores the challenge of crafting a democratic constitution under conditions of deep disagreement over a state's religious or secular identity. It draws on a broad range of relevant case studies of past and current constitutional debates in Europe, Asia, Africa and the Middle East, and offers valuable lessons for societies soon to embark on constitution drafting or amendment processes where religion is an issue of contention.